England in Particular. A Celebration of the Commonplace, the Local, the Vernacular and the Distinctive - Clifford S. Sue (London, Hodder & Stoughton, 2006)
Abbeys, allotments, apples, barns, beach huts, brass bands, chalk stteams, cheese rolling, cooling towers, cream teas, damsons, dialects, drystone walls, eels, fell running, field names, fish & chips, gargoyles & grotesques, giants, Gypsies, hawthorn, heronries, ings, jet, kippers, letterboxing, lidos, Martello towers, maypoles, mosques, nobbies, nurseries, oysters, Pancake Day, pele towers, quicksand, red squirrels, rhubarb, sheep, smells, starlings, terraced houses, terriers, topiary, unlucky words, vineyards, warrens, weather, white horses, yew, zigzags...England is a land of extraordinary variety, rich in buildings, landscapes, peoples and wildlife. But this diversity is under siege. Mass production, fashion, increased mobility and the forceful promotion of corporate identity have brought with them standardised shop fronts, farm buildings, factories, forests and front doors, while intensive farming has created a bland, empty countryside.This book is a counterblast against loss and uniformity, and a celebration of just some of the distinctive details that cumulatively make England. It is the culmination of more than twenty years work by Sue Clifford and Angela King, who founded Common Ground with Roger Deakin. Since 1982 this innovative charity has been encouraging us to appreciate and stand up for what is significant about our surroundings. Seen from the Common Ground perspective, things need not be conventionally picturesque, rare or spectacular to be special - there is value and local meaning to be found in cakes, cliffs, cooling towers and cuckoos. ENGLAND IN PARTICULAR offers a way of looking that make? the mundane magical. It will change the way you see the world.